Análise ergonômica do trabalho no setor de reciclagem automotiva: estudo de caso em uma empresa de desmontagem de ônibus - Thorgaard, Anna Carolina Pimenta (Universidade Federal de São Carlos, 2025)
The automotive recycling sector, within the logic of the circular economy, presents significant ergonomic challenges that directly affect workers' health, well-being, and performance. This study aims to analyze working conditions in a company specialized in bus dismantling, focusing on identifying ergonomic risks and the gap between prescribed work and actual work. The research was conducted through a qualitative case study, involving semi structured interviews with workers and managers, as well as the application of the Task Description Sheet (FDT) and the Ergonomic Workplace Analysis (EWA), following the principles of activity-centered ergonomics. The results reveal several shortcomings in working conditions, including excessive physical effort, awkward postures, limited use of personal protective equipment, task improvisation, and exposure to unhealthy environments. The workers' routine is marked by informal adaptations and physical overload, highlighting the need for ergonomic interventions that promote safer, healthier, and more productive workplaces. It is concluded that the adoption of participatory ergonomic strategies can contribute to reducing occupational risks and improving quality of life at work.
Ergonomic analysis in the automotive recycling sector: a case study in a bus dismantling company
Keywords: Ergonomia da atividade; Análise ergonômica do trabalho; Saúde ocupacional; Setor automotivo; Reciclagem de ônibus; Activity-centered ergonomics; Ergonomic work analysis; Occupational health; Automotive sector; Bus recycling; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO